Biomarkers and the Prediction of Adverse Outcomes in Preeclampsia: A Systematic Review and Meta-Analysis. Issue 1 (March 2022) - Lim, S.; Li, W.; Kemper, J.; Nguyen, A.; Mol, B.W.; Reddy, M.
Abstract : ( Obstet Gynecol . 2021;137:72–81. doi: 10.1097/AOG.0000000000004149) Progress has been made recently to predict and diagnose preeclampsia in pregnant women. Angiogenic and antiangiogenic biomarkers such as placental growth factor (PlGF) and soluble fms-like tyrosine kinase-1 (sFlt-1) have been examined and recently implemented clinically as predictive measurements of preeclampsia. This study aims to review and analyze sFlt-1, PlGF, and the sFLt-1/PlGF ratio and their ability to predict time to delivery and adverse outcomes in patients with preeclampsia.